2018
DOI: 10.1158/1940-6207.capr-17-0249
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Profiles of Hepatocellular Carcinoma in a Korean Prospective Cohort: The Korean Cancer Prevention Study-II

Abstract: In the prospective Korean Cancer Prevention Study-II (KCPS-II), we investigated the application of metabolomics to differentiate subjects with incident hepatocellular carcinoma (HCC group) from subjects who remained free of cancer (control group) during a mean follow-up period of 7 years with the aim of identifying valuable metabolic biomarkers for HCC. We used baseline serum samples from 75 subjects with incident HCC and 134 age- and gender-matched cancer-free subjects. Serum metabolic profiles associated wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
53
2
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 41 publications
7
53
2
9
Order By: Relevance
“…The metabolite classes included in treelet components 1 and 3 are structural components of cell membranes, and along with the related enzymes and intermediates they are involved in proliferation, cell signaling and cell survival, and thus may play key roles in carcinogenesis, progression and migration of tumors. 20,21,28 Their potential association may apply to cancer in general rather than being prostate cancer-specific; some prospective studies have reported lower risk of breast cancer, 9,29 colorectal cancer, 30 hepatocellular carcinoma 31,32 and pancreatic cancer 33 in relation to higher levels of phosphatidylcholines and related metabolites, while another study did not observe an association between the few included phospholipids and breast cancer risk. 34 Involvement in shared metabolic pathways may also explain the grouping of metabolites in treelet component 2.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolite classes included in treelet components 1 and 3 are structural components of cell membranes, and along with the related enzymes and intermediates they are involved in proliferation, cell signaling and cell survival, and thus may play key roles in carcinogenesis, progression and migration of tumors. 20,21,28 Their potential association may apply to cancer in general rather than being prostate cancer-specific; some prospective studies have reported lower risk of breast cancer, 9,29 colorectal cancer, 30 hepatocellular carcinoma 31,32 and pancreatic cancer 33 in relation to higher levels of phosphatidylcholines and related metabolites, while another study did not observe an association between the few included phospholipids and breast cancer risk. 34 Involvement in shared metabolic pathways may also explain the grouping of metabolites in treelet component 2.…”
Section: Discussionmentioning
confidence: 99%
“…Perak sulfat (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) merupakan senyawa ion dari perak dengan rumus Ag2SO4, yang digunakan dalam penyepuhan perak (silver plating) dan pengganti tanpa noda untuk perak nitrat. Garam sulfat ini stabil di bawah kondisi penggunaan dan penyimpanan biasa, meskipun ia menjadi gelap pada pajanan terhadap udara atau cahaya.…”
Section: Introductionunclassified
“…Perak Sulfat (Ag2SO4) (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) memiliki konduktivitas (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) . Besarnya nilai konduktivitas (1-10) ditentukan oleh konsentrasi elektrolit.…”
Section: Introductionunclassified
See 2 more Smart Citations